2010
DOI: 10.1038/ajg.2010.218
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Relapsing Mild-to-Moderate Ulcerative Colitis With the Probiotic VSL#3 as Adjunctive to a Standard Pharmaceutical Treatment: A Double-Blind, Randomized, Placebo-Controlled Study

Abstract: OBJECTIVES:VSL#3 is a high-potency probiotic mixture that has been used successfully in the treatment of pouchitis. The primary end point of the study was to assess the effects of supplementation with VSL#3 in patients affected by relapsing ulcerative colitis (UC) who are already under treatment with 5-aminosalicylic acid (ASA) and/or immunosuppressants at stable doses.METHODS:A total of 144 consecutive patients were randomly treated for 8 weeks with VSL#3 at a dose of 3,600 billion CFU/day (71 patients) or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
224
1
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(240 citation statements)
references
References 36 publications
5
224
1
10
Order By: Relevance
“…Evidence has shown that the administration of probiotics to patients suffering from IBD can restore the microbiota composition and induce beneficial effects (Ringel et al, 2012;Vanderpool et al, 2008). In patients suffering from UC, the clinical efficacy of probiotics was demonstrated by administration of VSL#3 that resulted in a remission in adult patients with active UC (Sood et al, 2009;Tursi et al, 2010) and in children (Miele et al, 2009). In addition, treatment with L. rhamnosus GG was effective in maintaining remission in patients suffering from UC (Zocco et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that the administration of probiotics to patients suffering from IBD can restore the microbiota composition and induce beneficial effects (Ringel et al, 2012;Vanderpool et al, 2008). In patients suffering from UC, the clinical efficacy of probiotics was demonstrated by administration of VSL#3 that resulted in a remission in adult patients with active UC (Sood et al, 2009;Tursi et al, 2010) and in children (Miele et al, 2009). In addition, treatment with L. rhamnosus GG was effective in maintaining remission in patients suffering from UC (Zocco et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that there is a lack of welldesigned, large, randomized, placebo-controlled trials that can certify that probiotics are effective in the prevention and treatment of IBD [125]. Additional studies such as the double-blind, randomized, placebo-controlled clinical trial of the treatment of relapsing mild-to-moderate ulcerative colitis with the probiotic VSL#3 as adjunctive to a standard pharmaceutical treatment [126] are required to confirm animal data and are necessary to convince the medical and general community of the benefits and potential application of probiotics in the prevention and treatment of IBD.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have focused on VSL#3, a high-potency probiotic mixture, in adult and paediatric UC. A recent Italian study in adults with UC demonstrated that VSL#3 supplementation was safe and effective, with reduction in disease activity scores and symptoms (Tursi et al 2010). An earlier paediatric study evaluated the same probiotic therapy in 29 children with newly-diagnosed active UC using a randomised placebocontrolled design (Miele et al, 2009).…”
Section: Novel Therapies For Ucmentioning
confidence: 99%